New Polish Atomic Energy Act Governmental Draft – No. 1724 - Szkultecka, Ewa (Contemporary Oncology/Współczesna Onkologia, 2000)
The draft of the new Polish Atomic Energy Act is discussed. A special attention is payed on the basic radiation protection measures that should be observed in activities connected with ionizing radiation, and that are settled in draft according to the Council Directive 96/29/Euratom of 1996.